Evaluación espaciotemporal de contaminantes atmosféricos en la ciudad de Barranquilla (2020)
Air pollution has become a critical issue in urban areas, so a broad understanding of its spatiotemporal characteristics is required. In the present study, continuous measurements in real time of atmospheric pollutants of particulate matter (PM10 and PM2.5) and ozone (O3), were carried out between March 2018 and June 2019, in three (3) monitoring stations localized in Barranquilla city. The Móvil station is located in the north area near the sea, Policía located in the south and influenced by high vehicular traffic and Tres Avemarías in the north-historic center in a residential area were evaluated. The average concentrations observed for Móvil, Policía and Tres Avemarías stations, respectively, for PM10 were: 46.37, 51.37 and 39.68 µg/m3; PM2.5: 15.95, 18.12 and 15.10µg/m3 and O3: 34.99, 26.56 and 33.63 µg/m3. The results indicated the existence of spatial and temporal variations between the stations and the pollutants evaluated. The highest PM concentrations were observed in the south of the city, while for ozone in the north. These variations are mainly associated with the influence of local sources in the environment of each site evaluated as well as the meteorological conditions of the study area. This research will help to establish the air quality baseline for Barranquilla, as well as enable the development of more effective Environmental Management plans.